Comparative Whole Genome Sequence Analysis and Biological Features of Clostridioides difficile Sequence Type 2‡ - Xu, Xingxing; Bian, Qiao; Luo, Yun; Song, Xiaojun; Lin, Shan; Chen, Huan; Liang, Qian; Wang, Meixia; Ye, Guangyong; Zhu, Bo; Chen, Liang; Tang, Yi-Wei; et al. (Frontiers in Microbiology, 2021)
Clostridioides difficile sequence type 2 (ST2) has been increasingly recognized as one of the major genotypes in China, while the genomic characteristics and biological phenotypes of Chinese ST2 strains remain to be determined. We used whole genome sequencing and phylogenetic analysis to investigate the genomic features of 182 ST2 strains, isolated between 2011 and 2017. PCR ribotyping (RT) was performed, and antibiotic resistance, toxin concentration, and sporulation capacity were measured. The core genome Maximum-likelihood phylogenetic analysis showed that ST2 strains were distinctly segregated into two genetically diverse lineages (L1 [67.0% from Northern America] and L2), while L2 further divided into two sub-lineages, SL2a and SL2b (73.5% from China). The 36 virulence related genes were widely distributed in ST2 genomes, but in which only 11 antibiotic resistance associated genes were dispersedly found. Among the 25 SL2b sequenced isolates, RT014 (40.0%, n=10) and RT020 (28.0%, n=7) were two main genotypes with no significant difference on antibiotic resistance (χ2=0.024-2.667, P > 0.05). A non-synonymous amino acid substitution was found in tcdB (Y1975D) which was specific to SL2b. Although there was no significant difference in sporulation capacity between the two lineages, the average toxin B concentration (5.11±3.20 ng/µL) in SL2b was significantly lower in comparison to those in L1 (10.49±15.82 ng/µL) and SL2a (13.92±2.39 ng/µL) (χ2=12.30, P < 0.05). This study described the genomic characteristics of C. difficile ST2, with many virulence loci and few antibiotic resistance elements. The Chinese ST2 strains with the mutation in codon 1975 of the tcdB gene clustering in SL2b circulating in China express low toxin B, which may be associated with mild or moderate C. difficile infection.